Studies on Campylobacter sputorum subspecies mucosalis - Lawson, G. H. K.; Rowland, A. C.; Roberts, L. (Journal of Medical Microbiology, 1976)
Summary Catalase-negative vibrios can be isolated in large numbers from the affected intestinal mucosa of pigs suffering from a range of porcine enteropathies in which the mucosa has an adenomatous component. These vibrios cannot be distinguished from strains of Campylobacter sputorum subsp. mucosalis. The resemblance between these bacteria strengthens the case already made on morphological evidence that these enteropathies have a common origin. Catalase-negative vibrios have also been isolated from the mouth and faeces of pigs. Some of these conform to the criteria established for the mucosalis subspecies but others can be differentiated from it. An antigenic analysis shows that strains of the mucosalis subspecies are closely related antigenically, but that differences may allow separation of strains.